THE INTERRELATIONSHIP OF PHYSICAL QUALITIES OF YOUNG VOLLEYBALL PLAYERS - o‘g‘li, Tojiyev Ulug‘bek Mamadiyor; qizi, Narzullayeva Gulmida Jasur (Research Focus International Scientific Journal, 2026)
The importance of physical qualities in training young volleyball players is discussed. The specific physical qualities of different sports differ from one another. The interrelationship of the physical qualities of volleyball players is also covered.